2016
DOI: 10.1111/jgs.14331
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Masticatory Dysfunction and Mortality in Community Dwelling Elderly Adults: A 9‐Year Follow‐Up

Abstract: OBJECTIVES: To evaluate the association, if any, between masticatory dysfunction (MD) and mortality in older adults. DESIGN: The Invecchiare in Chianti (InCHIANTI) Study, a cohort study with 9-year follow-up. SETTING: Tuscany, Italy. PARTICIPANTS: Individuals aged 65 and older (N = 1,155). MEASUREMENTS: MD was self-reported; Cox regression was used to assess the association between self-reported MD and 9-year all-cause mortality. This association was also evaluated after stratifying according to use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…The results of that study showed that masticatory dysfunction acted independently of serum levels of albumin on the risk of mortality. Nutrition is not only a matter of chewing ability but also depends on other influencing factors [39], and a systematic review concluded that chewing ability explains only part of the variance in food and nutrient intake by older adults [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of that study showed that masticatory dysfunction acted independently of serum levels of albumin on the risk of mortality. Nutrition is not only a matter of chewing ability but also depends on other influencing factors [39], and a systematic review concluded that chewing ability explains only part of the variance in food and nutrient intake by older adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…", "Has the amount of food you usually eat decreased in the last year because of chewing problems?" [39] and "Can you chew any type of food?" [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a stable indicator with minor variation over time [ 72 ]. It can be the predictor or a risk factor for mortality in older adults [ 18 , 19 , 20 , 21 ]. In this study, self-assessed chewing ability was statistically significant for women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired oral function and dysphagia increases the risk of aspiration pneumonia and choking [ 16 , 17 ]. Several studies have suggested that self-assessed chewing ability or mastication deficiency is a risk for mortality [ 18 , 19 , 20 , 21 ]. However, for addressing oral health and nutrition, well-designed studies are still not enough [ 22 ].…”
Section: Introductionmentioning
confidence: 99%